Peristiwa Galung Lombok 1946-1947 - Herlina, Herlina (Universitas Negeri Makassar, 2018)
This study aims to describe the background of the occurrence of historical events that occurred in 1946-1947 at Galung Lombok Polewali Mandar, West Sulawesi, namely the massacre carried out by Westerling's forces under Vermeulen Leadership which resulted in casualties consisting of fighters and civilians and this research aims to reconstruct the Galung Lombok incident in the Tinambung District of Polewali Mandar District and find out the impact of the Galung Lombok incident in an effort to uphold and maintain the Independence of the Republic of Indonesia in South Sulawesi. This type of research is a qualitative descriptive analysis using historical methods. Data collection techniques used are document collection, observation, interviews, and documentation. the results showed that the Galung Lombok incident was a Mandar massacre which took place on February 1, 1947 and could be seen from three phases, in which the first phase of the execution was the execution of 32 Mandar fighters detained in the Majene KNIL prison. Second phase: shooting dead people suspected of being extremists, and third phase; The cleansing tragedy itself. The results showed that the Galung Lombok incident was a tragedy of the Mandar massacre which was motivated by the Dutch government's desire to reinvest its power in Indonesia, especially in the Mandar region. Because the wishes of the Dutch government in South Sulawesi were strongly rejected by the fighters in various regions and resulted in resistance from firefighting fire against the Dutch government in Sulawesi, it was the background that issued a decree of martial law (Staat Van Oorlog en Beleg) in force. for Afdeling Makassar, Bonthain, Pare-pare and Afdeling Mandar and bring down Westerling and Special Forces or Special Topen Datasemen (DST). This event has caused various impacts on the community, especially the families of the victims.